Scientific basis of ISO standards on biomechanical risk factors - Armstrong, Tom J; Burdorf, Alex; Descatha, Alexis; Farioli, Andrea; Graf, Maggie; Horie, Seichi; Marras, William S; Potvin, Jim R; Rempel, David; Spatari, Giovanna; Takala, Esa-Pekka; Verbeek, Jos; et al. (Scandinavian Journal of Work, Environment & Health, 2018)
Among other purposes, companies and regulatory agencies from around the world often adopt International Standard Organization (ISO) standards to determine acceptable practices, equipment and criteria for preventing occupational injuries and illnesses. ISO standards are based on a consensus among individuals who participate in the process. This discussion paper examines the scientific process for the development of several ISO standards on biomechanical factors, comparing it with processes used by other professional organizations, including scientific committees working on the development of clinical guidelines. While the ISO process has value, it also has clear limitations when it comes to developing occupational health and safety standards that should be based on scientific principles.
Keywords: biomechanical; biomechanical risk factor; evidence-based practice; ISO; ISO standard; prevention; risk assessment; risk factor